2024 Election Organizers Recruitment Reform: Challenges and Solutions Towards More Transparent and Accountable Elections - Rizky Dwi Kusuma; Riski Puspita Lestari (Journal of Government and Political Issues, 2023)
This study evaluates the recruitment scheduling of election organizers in Indonesia, particularly in the context of the 2024 General Elections. It highlights the challenge posed by the short interval, often around two years, between recruitment and the conduct of elections, especially at the Provincial and Regency/City levels. To address this, the study recommends extending the tenure of organizers whose terms end in 2023 and 2024 until the election stages are completed and accelerating the recruitment for those whose terms end during the election process. It also emphasizes the importance of the selection team's composition, advocating for neutrality and the involvement of the Election Organizer Ethics Council (DKPP) and the Regional Examination Team (TPD) to ensure high-integrity candidates. These measures aim to enhance the recruitment quality and ensure the efficient execution of elections, thereby strengthening Indonesia's electoral system.